Patterned Optoelectronic Tweezers: A New Scheme for Selecting, Moving, and Storing Dielectric Particles and Cells. Issue 45 (11th October 2018) - Zhang, Shuailong; Shakiba, Nika; Chen, Yujie; Zhang, Yanfeng; Tian, Pengfei; Singh, Jastaranpreet; Chamberlain, M. Dean; Satkauskas, Monika; Flood, Andrew G.; Kherani, Nazir P.; Yu, Siyuan; Zandstra, Peter W.; et al.
Abstract: Optical micromanipulation has become popular for a wide range of applications. In this work, a new type of optical micromanipulation platform, patterned optoelectronic tweezers (p‐OET), is introduced. In p‐OET devices, the photoconductive layer (that is continuous in a conventional OET device) is patterned, forming regions in which the electrode layer is locally exposed. It is demonstrated that micropatterns in the photoconductive layer are useful for repelling unwanted particles/cells, and also for keeping selected particles/cells in place after turning off the light source, minimizing light‐induced heating. To clarify the physical mechanism behind these effects, systematic simulations are carried out, which indicate the existence of strong nonuniform electric fields at the boundary of micropatterns. The simulations are consistent with experimental observations, which are explored for a wide variety of geometries and conditions. It is proposed that the new technique may be useful for myriad applications in the rapidly growing area of optical micromanipulation. Abstract : Patterned optoelectronic tweezers (p‐OET), a technique that is useful for selecting, moving, and storing dielectric particles and cells, is introduced. In p‐OET devices, a portion of the photoconductive layer that is present in conventional OET devices is patterned, forming structures useful for repelling unwanted particles/cells, and also for keeping selected particles/cells in place after turning off the light source.